Developing the Global Self: A Developmental-Psychological Analysis of Identity Negotiation and Adaptation in Intercultural Learning Environments - Muhammad Habib Nabil Hermansyah; Rayhan Firasyan Riyadi; Firman Alief Firdausy Hidayat; Rafiqi Nur Ahmadi Hidayat; Ummi Masrufah Maulidiyah (P3I UMSurabaya, 2025)
This systematic literature review examines the psychological processes underlying global identity development in intercultural learning environments. Using thematic synthesis methodology, this study analyzes peer-reviewed articles published between 2023-2024 from databases including PsycINFO, PubMed, ERIC, and Web of Science. Drawing from developmental and cross-cultural psychology frameworks, the review synthesizes recent research on identity negotiation, psychological adaptation, and global self-concept formation among individuals navigating multiple cultural contexts. Findings reveal that global identity development is a dynamic process influenced by bicultural identity integration, psychological adjustment mechanisms, and environmental factors. Successful identity negotiation correlates with positive psychological outcomes, including enhanced well-being, academic achievement, and intercultural competence. This review contributes to understanding how educational systems can support healthy global identity formation through culturally responsive pedagogical approaches.